Efikasi Statin pada Tata Laksana Oftalmopati Graves: Analisis - Ekaputri, Maria Vania Tri; Tanu, Megawati (PT Kalbe Farma Tbk., 2025)
Graves’ ophthalmopathy (OG) is an ocular manifestation of autoimmune thyroid disease. The inflammation and tissue remodeling of OG can cause mild to severe symptoms that can damage the nerves in the eye and lead to blindness. Early identification of diagnosis, classification of activity and severity of the disease, and risk factors for the disease are crucial. Those steps can support comprehensive further management to prevent severe and permanent damage. The complex interactions between endogenous (unmodifiable), exogenous (modifiable), and environmental factors play as risk factors for OG development. Hypercholesterolemia which is also caused by long-term systemic inflammation is one of the risk factors associated with OG. Hypercholesterolemia can be treated by administering statin. Beside it’s role in lowering cholesterol level, statins have preventive and therapeutic effects especially in patient with active moderate to severe OG. Statin also have pleiotropic effects, act as immunoregulator, inhibiting adipogenesis and synergize with methylprednisolone in management of OG.